Association of dietary fatty acids and the incidence risk of cardiovascular disease in adults: the Tehran Lipid and Glucose Prospective Study - Parvin Mirmiran; Zeinab Houshialsadat; Zahra Bahadoran; Sajad Khalili-Moghadam; Farhad Sheikholeslami; Fereidoun Azizi (BMC, 2020)
Abstract Background Considering the inconsistent available findings regarding the cardioprotective effect of dietary fatty acid composition, we prospectively examined the feasible association between the dietary fatty acids and the cardiovascular disease (CVD) incidence in framework of the population-based Tehran Lipid and Glucose Study. Methods A total of 2369 participants (19-70 years, 43.5% men) without CVD at baseline (2006-2008) were included and followed-up for 6.7 years. Fatty acids' dietary intake was estimated using a 168-item semi-quantitative food frequency questionnaire. The CVD incidence risk across tertiles of dietary fatty acids was predicted via Cox proportional hazards regression models. Results The average age and body mass index of the included population were 38.5 ± 13.3 years and 26.6 ± 4.8 kg/m2 at baseline. Over 6.7 years of follow-up, 79 cases of CVD were detected. The risk of CVD was lower in upper tertile of monounsaturated fatty acids, oleic acid, and docosahexaenoic acid + eicosapentaenoic acid among the tertiles. No significant associations were found between total fat, saturated and polyunsaturated fatty acids' intake, and CVD. Conclusions Our results suggest that the dietary fatty acid composition might affect the incidence risk of CVD within the Iranian population.